The Influence of Good Corporate Governance, Risk Management, and Company Size on Financial Performance in the Banking Sector Listed on the Indonesia Stock Exchange - Siti Meirini Dwi Ningsih; Muizzuddin; Kemas Muhammad Husni Thamrin (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to analyze the partial and simultaneous influence of Good Corporate Governance (GCG), Risk Management, and Company Size on Financial Performance (Return on Assets/ROA) in 47 banking companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The main issue is the inconsistency of banks' financial performance amidst the challenges of digitalization and rampant governance cases, which reinforces the urgency of implementing effective GCG and risk management. The method used is Panel Data Regression analysis with a Random Effects model, which meets the classical assumptions (Normality, Multicollinearity, Autocorrelation, and Heteroscedasticity). The F-test results indicate that GCG, Risk Management, and Company Size simultaneously have a significant effect on Financial Performance with an R2 value of 33.26%. Partially, the variables Independent Commissioners, Audit Committee, Non-Performing Loans (NPL), BOPO, and Company Size were found to have a significant effect on ROA. Meanwhile, Institutional Ownership, Managerial Ownership, and Net Interest Margin (NIM) did not have a significant impact. The conclusion confirms that strengthening GCG mechanisms (Independent Commissioners and Audit Committees), credit risk control (NPL), operational efficiency (BOPO), and utilizing economies of scale (Company Size) are key factors in increasing bank profitability in Indonesia.